2020
DOI: 10.1039/c9ra09516k
|View full text |Cite
|
Sign up to set email alerts
|

Efficient deoxygenation of waste cooking oil over Co3O4–La2O3-doped activated carbon for the production of diesel-like fuel

Abstract: Untreated waste cooking oil (WCO) with significant levels of water and fatty acids (FFAs) was deoxygenated over Co3O4–La2O3/ACnano catalysts under an inert flow of N2 in a micro-batch closed system for the production of green diesel.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
22
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 62 publications
(24 citation statements)
references
References 59 publications
2
22
0
Order By: Relevance
“…From XRD analysis (spectra not shown), Co 3 O 4 and Fe 2 O 3 were detected as the active phases on activated carbon. Similar observation was also reported in [12].…”
Section: Results and Discussion 31 Characterization Of Catalystsupporting
confidence: 91%
See 2 more Smart Citations
“…From XRD analysis (spectra not shown), Co 3 O 4 and Fe 2 O 3 were detected as the active phases on activated carbon. Similar observation was also reported in [12].…”
Section: Results and Discussion 31 Characterization Of Catalystsupporting
confidence: 91%
“…6 shows the carbon number selectivity for C 5 -C 20 hydrocarbons content in liquid product obtained by using the Fe/AC catalysts with different Fe loading. Liquid product exhibited more selectivity for n-(C 15 + C 17 ) hydrocarbons and it could be deduced as the consequence of deoxygenation of palmitic acid (C 16 ) and oleic acid (C 18 ) in WCO via decarboxylation and/or decarbonylation [12]. The highest n-(C 15 + C 17 ) hydrocarbons selectivity (52 %) was detected for 7.5-Fe/AC which was also in line with the highest liquid yield obtained.…”
Section: Effect Of Metal Loading On Ac 321 Fe Loadingsupporting
confidence: 66%
See 1 more Smart Citation
“…It was found that the primary absorption bands of WCO were at 1120 cm À1 , 1740 cm À1 , and 2922 cm À1 , and these were attributed to the carbonyl group (C-O-C), the ester group (C]O), and the stretching absorption of the C-H bond, respectively. 67 It also showed that the deoxygenated liquid products rendered a carboxylic acid (-COOH) group peak at 1711 cm À1 , indicating that the deoxygenation of WCO was initiated by breaking the ester bond of triglycerides. The successful progression of deoxygenation activity was also in accordance with the disappearance of the carbonyl group (C-O-C) absorption band at 1120 cm À1 .…”
Section: Deoxygenation Activity Of Wcomentioning
confidence: 97%
“…The authors investigated the catalytic conversion reaction pathways that were used in the production of biodiesel fuels through two specific approaches containing experimental approach and theoretical approach. Finally, the authors described the potential of various thermocatalytic pathways that could be effectively used in the production process of producing biodiesel fuels through computational modeling techniques that were directed to elucidate the major information associated with the optimization of the conversion process [42,43]. The authors described the pathways that were used for the production of biodiesel fuels through the utilization of microalgae in association with carbohydrates, lipids and proteins as shown in Fig.…”
Section: Recent Progress Of Do Of Realistic Green Oil Worldmentioning
confidence: 99%